COVID-19 and Food Safety FAQ: Is Coronavirus a Concern on Fresh Produce? - Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman; Michelle Danyluk (EDIS)
CDC, FDA and USDA are not aware of any reports at this time of human illnesses that suggest coronavirus can be transmitted by food or food packaging. However, it is always important to follow good hygiene practices (i.e., wash hands and surfaces often, separate raw meat from other foods, cook to the right temperature, and refrigerate foods promptly) when handling or preparing foods. This flyer, written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman (NC State University Extension), provides answers to some frequently asked questions about coronavirus and fresh produce. Published by the UF/IFAS Food Science and Human Nutrition Department, March 2020.